The effects of Kisspeptin antibodies on delayed estrus in rats - Risvanli, Ali; Apaydin, Ali Mukremin; Bulut, Hakan; Timurkaan, Necati; Saat, Nevzat (Informa Healthcare, 2010)
In recent years, numerous studies have been conducted on the effects of Kisspeptin/GPR54 system on sexual cycle, which proved that this system regulated gonadotropin release through GnRH. This study aims to determine the effects of hyperimmune serum containing antibodies produced against Kisspeptin on the sexual cycle and GnRH receptors in rat pituitaries. To this end, five Wistar female rats were passively immunised using a hyperimmune serum obtained from two Wistar female rats against Kisspeptin 10. Another five rats were selected as the control group. Anti-Kisspeptin antibodies of the hyperimmunised rats in the serum were identified by ELISA. The sexual cycles of the rats were followed by the measurements of vaginal irrigations and the estradiol concentrations in their blood samples. The number of follicles and corpora lutea in their ovaries was determined through histopathological tests, and the GnRH receptors in their pituitaries were identified by immunohistochemistry. Consequently, strong seropositivity was detected in all passively immunised rats and the hyperimmune serum. However, no difference was found between the groups with regard to the number of estrous cycles observed, the interval between estrous periods, estradiol concentrations, the number of follicles and corpora lutea and immunohistochemical results.
Keywords: Kisspeptin; antibodies; estrus; rats